The Top 10 ethical challenges in dental practice in indian scenario: Dentist perspective - Vanishree M Kemparaj; Ganesh Shenoy Panchmal; Umashankar Gangadaraiah Kadalur (Wolters Kluwer Medknow Publications, 2018)
Aim: This exploratory qualitative research is an attempt to assess the health care ethical challenges in dental practice in an Indian scenario. Methodology: Qualitative indepth interview was conducted on 20 dental professionals to assess the ethical challenges prevailing in dental practice in Indian scenario. After obtaining the responses the verbatims were categorized into categories and finally 36 themes emerged. Later from two group of 6 panellists each after conducting focus group discussion the themes of ethical issues occurring in dental practice were ranked based on order of significance impact on the practice, patient and society using Delphi method. Result: The top ten ethical challenges listed by the panellists are inadequate sterilization and waste management in dental clinics, poor knowledge and attitude towards ethics among our dental practitioners, in competence among dental professional, increase in cost of oral health service, poor informed consent process, requirement of consensus about the treatment procedures among dentists, Conflict in Advertising, clustering of dental clinics in urban areas, disagreement with treatment modalities among dentist and patient, poor medical record maintenance among our dental practitioners. Conclusion: The study attempts to bring the prevailing ethical challenges in oral health care practice in Indian scenario.